Fetal aortic coarctation: A combination of third-trimester echocardiographic parameters to improve the prediction of postnatal outcome - Tuo, Giulia; Paladini, Dario; Marasini, Lucia; Buratti, Silvia; De Tonetti, Gabriele; Calevo, Maria G.; Marasini, Maurizio (Frontiers in Pediatrics, 2022)
Objectives: To determine a combination of third trimester echocardiographic parameters for improving prenatal prediction of Coarctation of the Aorta (CoA) after birth. Methods: All cases of CoA suspicion at fetal echocardiography performed at second and/or third trimester of pregnancy at Gaslini Children Hospital between January 2010 and December 2020 were included in the study. Last prenatal ultrasound evaluation was reviewed considering most of the echocardiographic criteria already published for prenatal CoA diagnosis. Associated minor cardiac anomalies as ventricular septal defect, persistent left superior vena cava (PLSCV) and redundant foramen ovale (FO) membrane were reported as well as postnatal outcome. Initial perinatal management was defined on the basis of prenatal echocardiographic CoA risk stratification. Neonates were divided into two groups depending on the presence or absence of CoA after birth. Results: Among 91 fetuses with CoA suspicion, 27 (30%) were confirmed with CoA after birth and underwent surgical repair. All cardiac parameters except redundant FO membrane and PLSCV showed significant correlation with CoA. Statistical analysis confirmed that cardiovascular disproportion with right predominance carries an increased risk for occurrence of CoA, especially if already evident at the second trimester ultrasound evaluation. Aortic valve (AV) z score and distal transverse aortic arch (TAA) z score resulted as the best predictors of CoA after birth. The best cut-off point for CoA discrimination with ROC analysis was an AV z-score of -1.25 and a distal TAA Z-score of -0.37. 44% of those without CoA were diagnosed with a cardiac defect not diagnosed in utero or with pulmonary hypertension or with a genetic syndrome. Conclusions: Current criteria for diagnosis of CoA in utero allow accurate diagnosis of most severe cases but the rate of false positive remains relatively high for milder cases. Combination of anatomic and functional echocardiographic parameters might help in stratifying the risk of CoA. We proposed the AV and the TAA diameter z score as best predictors of CoA after birth. Also neonates without CoA deserve proper monitoring at birth because prenatal evidence of significant cardiovascular discrepancy between right and left cardiac structures has an inherent risk for additional morbidity postnatally.